Contemporary Middle Eastern social reality into global art in Singapore Biennale - Mohammed Baker Mohammed Al-Abbas (Tanjong Malim, 2016)
Contemporary Middle Eastern social reality into global art in Singapore Biennale by Mohammed Baker Mohammed Al-Abbas